Perceptions on the Utilization of Mobile Technologies for Learning among Postgraduate Students - Ayotunde A. Falade; Gboyega Ayodeji Aladesusi; Oyeronke Olufunmilola Ogunlade (Indonesian Research Journal in Education |IRJE|, 2021)
This study determined the perceptions of the utilization of mobile technologies for learning among Postgraduate Students in Kwara State. The study adopted survey approach. The population for this study was made up of all the postgraduate students in Kwara State. Proportional sampling techniques were used to allocate a number of respondents in each school based on their estimated population using Israel Model. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of stastistical product and service solution (SPSS) version 20.0 at 0.05 level of significant. The findings indicated that postgraduate students had positive perception of the utilization and ease of use of mobile technologies for learning. No significant difference exists in the postgraduate students’ perception of the utilization of mobile technologies for learning based on gender and the field of study. The study concluded that learning can be enhanced among postgraduates’ students if appropriate mobile technologies are deployed for learning. Therefore, postgraduate students are encouraged to deploy mobile technology for learning irrespective of their gender.